Synthesizing green Chitosan-magnetic composite particles for palm oil mill effluent (POME) pre-treatment: a comprehensive review - Arumugam, Veknesh; Ismail, Muhammad Heikal; Asih, Ngadisih; Irie, Mami; Omar, Rozita (Elsevier BV, 2021)
Biopolymer is the most promising product for the cost-effective substitution of chemical coagulants with biodegradable products with favorable mechanical characteristics. Chitosan is a high molecular weight and charging density naturally organic polyelectrolyte (biopolymer), which is obtained from chitin's deacetylation from the crustaceans shell. Due to the applicability of this polymer for treatment in the palm oil mill effluent (POME), a wide range of papers on chitosan-magnetic composite particle synthesis for POME pre-treatment have been written. Chitosan and magnetic particles are cross-links together to satisfy the needs of high adsorption, regeneration, fast separation, and cost-effective treatment of wastewater. This would best POME pre-treatment cost-effectively and sustainably. The use of biodegradable materials attracted the industry alongside the increasingly global trend of biopolymers with low toxicity and durability. As biodegradable materials became the focus of the material scientists, this type of product became more apparent. This paper aims to provide a complete description of synthesizing chitosan-magnetic composite particles for POME pre-treatment. The reviewed article discusses the main results during the last decade which are classified into four groups as chitosan as a coagulant, magnetic particles, synthesizing chitosan-magnetic composite particles and POME pre-treatment.